“To Evangelize the Poor” : The Gospel According to Luke, Isaiah, and Origen - Kelly, James E. (Lumen et Vita, 2019)
In this essay, I will examine the scriptural basis for Origen’s interpretation of Luke 4:18-19 as an allusion to Jesus’ identity as savior, not as a call to social justice. I argue that this interpretation is consistent with the intentions of the gospel writer. The essay begins with an analysis of the gospel writer’s redaction of Mark 1 in Luke 3-5. Based on that redaction, I hypothesize that Luke intends to emphasize Jesus’s identity with the anointed one mentioned in Isaiah 61:1-2. This excerpt from Isaiah not only gives Luke 4:18-19 its Christological significance but also clarifies Luke’s understanding of poverty in relation to the Gospel. I then examine Origen’s application of the Lucan passage for his pastoral purposes. To conclude, I suggest that we, like Luke and Origen, read Scripture Christocentrically in order to better facilitate the church’s encounter with Christ during the liturgy.